The Role of Content Marketing, Discounts, and Live Streaming in Digital Purchasing Decisions - Zainul arifin (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of three independent variables—Content Marketing, Live Streaming, and Price Discount on the dependent variable of Purchase Decision. The results of the path analysis show that Content Marketing and Price Discount have a significant influence on Purchasing Decisions, with path coefficients of 0.499 and 0.382, respectively. Meanwhile, Live Streaming did not show a statistically significant effect on Purchasing Decisions. This research model has very strong learning power with an R-square value of 0.845, indicating that 84.5 % of the variation in Purchasing Decisions can be explained by the three independent variables.